Understanding peatland restoration costs and contractor capacity - Glenk, Klaus; McBride, Andrew; Urban, Daniel; Glendinning, James; Fletcher, Daniel; Moxey, Andrew; Martin-Ortega, Julia (SRUC, 2025)
Degraded peatlands are one of the largest sources of greenhouse gas emissions in Scotland. This research explored the evidence for peatland restoration costs in Scotland and examined emerging trends. It also investigated opportunities and challenges for contractors delivering peatland restoration services. We reviewed existing literature and analysed cost data compiled by SRUC from the PA programme projects supported by NatureScot funding between 2018 and 2023. We also carried out interviews with contractors. Data from other PA delivery partners post 2021 was not examined in this project phase due to time constraints
Keywords: Peatland; restoration; climate change; Scotland; costs; PeatlandACTION